EMPLOYEE JOB SATISFACTION AND ITS RELATIONSHIP TO MOTIVATION, COMMUNICATION, AND JOB STRESS - Imas Komariyah; Meita Sondang Riski; Kania Laelawati (SEAN Institute, 2023)
Human resources management is all activity relate to the recognitions of the importances of work motivations which will affects communications on employees job satisfactions and minimized the occurrence of works stress problems for employees. , utilizing function and activities that ensuring that human resources are utilizing effective and or for the benefit of individuals, companies and society. This studies aims to determine the effects of motivations, communications and works stress on job satisfactions of employees of PT Bravo Engineering Batam. This researches designed using researches designed and quantitatives researches methods. The data collections techniques is by distributed questionnaires to 115 respondents. The results of this studies indicated that motivation, communication and work stress partial and simultant has a significants effects on employee job satisfactions. The results of the coefficient of determination test indicate that motivation, communication and work stress affect job satisfaction by 51,3 percent, while the rest is influenced by other variables not examined in this study